Ð’Ð¿Ð»Ð¸Ð² Ñ‚ÐµÐ¼Ð¿ÐµÑ€Ð°Ñ‚ÑƒÑ€Ð¸ Ð½Ð° ÐºÐ¾ÐµÑ„Ñ–Ñ†Ñ–Ñ”Ð½Ñ‚Ð¸ Ð¿Ñ€Ð¾Ð½Ð¸ÐºÐ½Ð¾ÑÑ‚Ñ– Ð¼ÐµÐ¼Ð±Ñ€Ð°Ð½ Ð´Ñ€Ñ–Ð¶Ð´Ð¶Ñ–Ð² Saccharomyces cerevisiae Ð´Ð»Ñ Ð²Ð¾Ð´Ð¸ Ñ– ÐºÑ€Ñ–Ð¾Ð¿Ñ€Ð¾Ñ‚ÐµÐºÑ‚Ð¾Ñ€Ñ–Ð² - Sakun, A. V.; Maruschenko, V. V.; Kovalenko, I. F.; Sirenko, A. Yu.; Vysekantsev, I. P.; Davydova, E. V.; Gordiyenko, O. I. (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2009)
The biophysical parameters of yeast cell Saccharomyces cerevisiae, osmotically inactive volume, filtration coefficients in the cryoprotectant containing media and permeability coefficients for the cryoprotectants glycerol, 1,2-propane diol, dimethyl sulfoxide, were determined at the temperatures of 25 and 10Â°C. For determination of the parameters the improved equations of mass transfer via cell membranes were used. The equations are based on the approach of linear thermodynamics of irreversible processes. The values of activation energy of water and cryoprotectants molecules penetration via cell membranes were calculated.